Phylogeographic structure in the apparent absence of barriers: a case study of the Mexican land snail Humboldtiana durangoensis (Pulmonata: Humboldtianidae). (27th February 2019) - López, Benjamín; Zúñiga, Gerardo; Mejía, Omar
Abstract: It has been postulated that Pleistocene climatic change has promoted repeated contraction and expansion of the distributions of montane taxa in Mexico ('see-saw effect'). Under such a scenario, we would expect taxa, particularly those with limited dispersal such as land snails, to exhibit strong phylogeographic structure. Using an approach based on four molecular markers (COI, 16S, ITS1 and ITS2), we investigated the phylogeography of Humboldtiana durangoensis, a land snail endemic to the Madrean central region of the Sierra Madre Occidental of Western Mexico. We sampled a total of 178 individuals from 16 localities spanning the known geographic range of the taxon. Two main groups of H. durangoensis were recovered, one occupying the northern part of the current range of the species and the other the southern part. While these two groups show high haplotypic diversity and low nucleotidic diversity, suggesting a recent demographic expansion, our Bayesian Skyline Plots point to a more complex demographic history, involving expansion and contraction of the effective population size. The phylogeographic structure of H. durangoensis in the Sierra Madre Occidental may possibly be a result of Pleistocene climatic changes.